Asymmetric synthesis of (S)-phenylacetylcarbinol – closing a gap in C–C bond formation. Issue 2 (31st October 2016) - Sehl, Torsten; Bock, Saskia; Marx, Lisa; Maugeri, Zaira; Walter, Lydia; Westphal, Robert; Vogel, Constantin; Menyes, Ulf; Erhardt, Martin; Müller, Michael; Pohl, Martina; Rother, Dörte
Abstract : By the combination of biocatalyst design and reaction engineering, the so far not stereoselectively accessible ( S )-phenylacetylcarbinol could be enzymatically synthesized with product concentrations >48 g L −1 and an enantiomeric excess up to 97%. Abstract : ( S )-Phenylacetylcarbinol [( S )-PAC] and its derivatives are valuable intermediates for the synthesis of various active pharmaceutical ingredients (APIs), but their selective synthesis is challenging. As no highly selective enzymes or chemical catalysts were available, we used semi-rational enzyme engineering to tailor a potent biocatalyst to be >97% stereoselective for the synthesis of ( S )-PAC. By optimizing the reaction and process used, industrially relevant product concentrations of >48 g L −1 (up to 320 mM) were achieved. In addition, the best enzyme variant gave access to a broad range of ring-substituted ( S )-PAC derivatives with high stereoselectivity, especially for meta -substituted products.